2022
DOI: 10.3897/neobiota.76.85973
|View full text |Cite
|
Sign up to set email alerts
|

Do non-native and dominant native species carry a similar risk of invasiveness? A case study for plants in Turkey

Abstract: Most risk analysis studies in invasion biology have focused on the invasiveness of non-native species, even though some native species also can pose a high risk to the environment and human well-being. This is especially true under current global change, which may cause dominant native species to expand their range of distribution and have substantial effects on the ecosystem. In this study, the risk of invasiveness of five non-native and five native plant species in Turkey was evaluated using a standard risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
(89 reference statements)
0
6
0
1
Order By: Relevance
“…In other words, some native species have the potential to exhibit unchecked, aggressive growth, which can disrupt ecosystems and reduce floral diversity as effectively as invasive nonnative species. Yazlik and Ambarli (2022) showed that nonnative and dominant native species in Turkey carry a comparable risk of invasiveness. They suggest that dominant native species, shown to have negative environmental and socioeconomic impacts in their habitats, be included in priority lists for management strategies regardless of their origin or native status.…”
Section: T He Invasive Plants Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, some native species have the potential to exhibit unchecked, aggressive growth, which can disrupt ecosystems and reduce floral diversity as effectively as invasive nonnative species. Yazlik and Ambarli (2022) showed that nonnative and dominant native species in Turkey carry a comparable risk of invasiveness. They suggest that dominant native species, shown to have negative environmental and socioeconomic impacts in their habitats, be included in priority lists for management strategies regardless of their origin or native status.…”
Section: T He Invasive Plants Researchmentioning
confidence: 99%
“…Range-shifting native plants may behave like invasive plants and colonize new environments, resulting in potential negative consequences (Wallingford et al 2020). Also, Yazlik and Ambarli (2022) suggested that dominant native species shown to have negative environmental and socioeconomic impacts in their "home" habitats should be included in priority lists for management strategies regardless of their origin.…”
Section: T He Invasive Plants Researchmentioning
confidence: 99%
“…The burcucumber (Sicyos angulatus L.), an annual herbaceous vine belonging to the Sicyos genus in the Cucurbitaceae family, is native to North America [1]. This species exhibits a wide distribution across Europe and Asia due to its strong adaptability, high reproductive capacity, and diverse modes of dispersal [2,3,4]. Moreover, it has been observed in various regions such as Taiwan, Hebei, Liaoning, and Beijing [5, 6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Наибольшее видовое разнообразие Cuscuta наблюдается в субтропических и тропических зонах. Растения указанного рода встречаются, например, в Ираке [2], Иране [3,4], Китае [5], Ливане [6], Нигерии [7], Египте [8,9], Индии [10,11], Италии [12,13], Тунисе [14], Турции [15,16], России [17]. Из видового разнообразия рода Cuscuta можно выделить такого представителя, как Cuscuta campestris (повилика полевая), который представляет собой интересный объект с точки зрения фитохимического изучения [18][19][20] и спектра биологической активности [21][22][23].…”
Section: Introductionunclassified